Pengaruh Motivasi Kerja dan Kepemimpinan Transformasional Terhadap Kinerja Pegawai: Pada Dinas Pendidikan Pemuda dan Olahraga Kabupaten Kaimana - Warinussy, Stepanus L.; Rante, Yohanes; Erari, Anita (Magister Manajemen Universitas Cenderawasih, 2023)
At the Kaimana Regency Youth and Sports Education Office it is known that there are still many employees who have less than optimal performance. The problems studied in this study are (1) How is work motivation, transformational leadership, and employee performance, (2) How much influence does work motivation have on employee performance, (3) How much influence does transformational leadership have on employee performance, (4) Is work motivation and transformational leadership simultaneously have an influence on employee performance. The purpose of this research is to (1) find out how work motivation, transformational leadership, and employee performance, (2) analyze the influence of work motivation and transformational leadership on employee performance partially or simultaneously. Data collection methods used are documentation and questionnaires. The analytical method used is instrument test (validity test and reliability test), percentage descriptive analysis, classic assumption test, multiple regression analysis, coefficient of determination, and hypothesis testing using SPSS 15 for Windows. The research results obtained multiple linear regression equation Y = 5.854 + 0.276 X1 + 0.431 X2. The result of the coefficient of determination (Adjusted R Square) is 0.509 meaning that 50.9% of the performance variable is influenced by work motivation and transformational leadership and the remaining 49.1% is influenced by other variables outside the research.